2009
DOI: 10.1177/1748048509339792
|View full text |Cite
|
Sign up to set email alerts
|

Towards an African Journalism Model

Abstract: Much of the scholarly literature regarding theories of journalism practice is premised on the tenets of the western model of liberal democracy. To the extent that this model is held to be universal, it hinders the analytical theorization of journalistic precepts that have evolved locally in most countries of the developing world. This article seeks to address this problem by exploring the evolution of what may be aptly characterized as the African journalism model. This model is grounded in oral discourse, cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…This tracks with a longer history of journalism model exportation, whereby models for practice are exported to contexts where journalism professionalization is thought to be particularly malleable (Golding 1977). However, because peace journalism has emerged in a mainly Euro-American academic context, there is reason to believe that its principles may not be extended to contexts like East Africa without modifications (Mabweazara 2018; Shaw 2009). This study engages this tension by examining peace journalism as individuals understand it in the contexts in which they are situated.…”
Section: Journalists’ Perceptions and The Hierarchy-of-influences Modelmentioning
confidence: 99%
“…This tracks with a longer history of journalism model exportation, whereby models for practice are exported to contexts where journalism professionalization is thought to be particularly malleable (Golding 1977). However, because peace journalism has emerged in a mainly Euro-American academic context, there is reason to believe that its principles may not be extended to contexts like East Africa without modifications (Mabweazara 2018; Shaw 2009). This study engages this tension by examining peace journalism as individuals understand it in the contexts in which they are situated.…”
Section: Journalists’ Perceptions and The Hierarchy-of-influences Modelmentioning
confidence: 99%
“…Misgivings over the Western model of journalism have increased calls for adoption of regionally suitable models of journalism, one of which is the call for a reflection on Afrocentric-style journalism. Shaw (2009: 492) argues that approaches suggesting the ‘non-existence of any journalistic precept unique to Africa’ problematically convey ‘the impression that what obtains, or remains, of journalism practice in Africa, is nothing but a holistic replica of the western liberal democracy model’. In Africa, the call for journalistic practices and pedagogies that recognise local cultural traditions reflects the growing anxieties over the inadequacies of the Western model of journalism as an appropriate lens through which to understand the African situation, particularly as that Western model was based on a different cultural understanding (Kasoma, 1996).…”
Section: Towards An Inclusive Approach To De-westernising African Jou...mentioning
confidence: 99%
“…Rodny-Gumede (2013: 131) highlights how scholars (e.g. Motsaathebe, 2011; Nyamnjoh, 2005; Sesanti, 2009), among others, have suggested that ‘African theory of journalism must be developed and that journalism training and curricula in Africa need to become more African and Africanised in such a way that journalism training can reflect the theory of journalism based on African values and moral philosophy, and African culture.’ Journalism scholars such as Shaw (2009) and Skjerdal (2012) suggest that common deep-rooted beliefs and traditions such as the Ubuntu philosophy may be a promising way to approach journalism education in Africa and address issues unique to the socio-cultural and political making of various African countries. Later, we highlight some shortcomings of the concept of Ubuntu as an approach to de-Westernising journalism on its own.…”
Section: Towards An Inclusive Approach To De-westernising African Jou...mentioning
confidence: 99%
“…Journalism in Africa has often been theorised from the prism of Global North's epistemology, ontology and methodology largely due to its colonial ancestry (Shaw 2009(Shaw , 2018. Thus, the actors, organizational routines, cultures and practices of journalism in Africa are viewed using a professional gaze that often fails to acknowledge the sociocultural dynamics within which it is practised, consumed and distributed.…”
Section: Genres Of Peripheral Journalism(s) In Africamentioning
confidence: 99%